The leader communication style and its effect on staff morale and job satisfaction in UiTM Jengka Pahang / Noor Adilah Busari - Busari, Noor Adilah (2014)
The purpose of this research is 10 identify the relationship between style of communication with morale and job satisfaction. This research also aims to determine the level of relationship between the perceived communication style of the leader on staff morale and job satisfaction. 35 questionnaires were distributed to staffs in UiTM Jengka, Pahang. The entire questionnaire gets returned back. Element of communication style involved in this research includes work friendly, animated, attentive, and communicator image. Statistical Package for Social Science (SPSS) version 20.0 was used to analyze the data.. Leader's communication style gained can increase staffs morale and job satisfaction to the company. The significant and positive correlation between communication style and morale, and job satisfaction indicated the research consistently identifies morale as a behavior that can be improved with appropriate leadership behaviors. The hypotheses were accepted as the significant and positive relationship existed between leader's communication style and staffs morale and job satisfaction in UiTM Jengka, Pahang. Last but not least, there are few recommendations from these finding in enhance leader's communication style and morale and job satisfaction of staffs.